Nicht nach Design: Rekombiniertes Eigentum im osteuropäischen Kapitalismus - Stark, David (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
We should not be surprised that reorganization in Eastern Europe is yielding new property forms that are neither statist nor private. The economies of East Central Europe are evolving in forms that are neither state capitalist nor market socialist. These are mixed economies not because there are state-owned firms and privately owned firms but because the typical firm is itself a combination of public and private property relations. What we find are new forms of property in which the properties of private and public are dissolved, interwoven, and recombined. Property in East European capitalism in recombinant property.